Професійна діяльність бухгалтера: етичні аспекти - Гуріна, Наталія Валеріївна; Грищенко, Т. С. (ВД «Гельветика», 2021)
У статті досліджено основні наукові, практичні та теоретичні аспекти професійної діяльності бухгалтера. Визначено суть професійної етики бухгалтера. Проаналізовано праці науковців щодо важливості регулювання етичних аспектів діяльності облікових працівників. Розглянуто нормативно-правове регулювання діяльності професії бухгалтера. Обґрунтовано вплив дотримання професійної етики під час формування облікової інформації та описано соціальну спрямованість професії бухгалтера. Визначено головну рису професії бухгалтера. Досліджено актуальні проблеми етичної регламентації діяльності бухгалтерів. Доведено необхідність дотримання фундаментальних професійних етичних вимог. Розглянуто принципи етики, визначені Кодексом етики професійних бухгалтерів. Описано пропозиції щодо поліпшення впровадження принципів етики.

The article examines the main scientific, practical and theoretical aspects of the professional activity of an accountant. The essence of professional ethics of an accountant is determined. The works of scientists on the importance of ethical regulation of accounting staff are analyzed. The normative-legal regulation of the activity of the accounting profession is considered. The influence of observance of professional ethics during the formation of accounting information is substantiated. The social orientation of the accounting profession is described. The process of formation of qualitative information is investigated, and also its importance is described. In order to succeed, an accountant needs business and professional qualities, various methods and techniques of management. But, on the other hand, accounting is a specific functional and applied economics. In such sciences, the human factor plays an extremely important role. In addition to accounting, this means that no assessments of the reliability, reliability and sufficiency of information generated in the accounting system can be made without taking this factor into account. The human factor includes intellectual and personal qualities: knowledge, abilities, intelligence, emotional and volitional sphere, character. These qualities have two features. First, it is the foundation on which the professional, managerial competence of an accountant is built. Secondly, they are much more difficult to correct: it is much more difficult to change the style of thinking or character than to learn the method of decision-making or the technology of accounting. An indicator of professionalism is a high level of cultural development in the relevant field. The presence and functioning of professional values and values in a particular field allows its employee to understand many professional situations related to his responsibilities, and correlate them with the current system of values. Every accountant has a responsibility to promote high standards of professional conduct and ensure compliance with ethical requirements; in case of non-compliance with such an organization, an investigation may be conducted and appropriate measures taken. In the interests of the profession and all its members, the public needs to be confident that non-compliance with the ethical requirements of accountants will be investigated and disciplined if necessary.
Keywords: професійна етика бухгалтера; кодекс етики професійних бухгалтерів; принципи етики; облікова інформація; етична регламентація; professional ethics of an accountant; code of ethics of professional accountants; principles of ethics; accounting information; ethical regulations